Worker displacement and labor market success: Evidence from forced labor conscription during WWII - Carola Stapper (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Disruptions of labor market trajectories have lasting effects on later economic success. One type of disruption that is understudied is displacement due to forced labor conscription, despite it still being a frequent event nowadays. I study the consequences of exposure to forced labor conscription for individuals' long-term labor market outcomes. I exploit that cohorts of Dutch civilians faced a differential probability of temporary labor coercion in Nazi Germany during WWII in a Regression Discontinuity Design. Using Dutch census data from 1971, I find that conscripted individuals have lower education, income, and likelihood of employment. Studying heterogeneous effects, I find that facing harsher conditions in Germany is associated with lower labor force participation and worse health. My findings suggest that the negative impact on labor force participation is mitigated when individuals are forced to work in similar sectors to those in the Netherlands, enhancing their ability to reintegrate into the workforce.
Keywords: N34; N44; J24; J47; 330; Labor Economic History; Labor Market Careers; Coercive Labor Market; Forced Labor; Health; Skills